2019
DOI: 10.3390/atmos10110684
|View full text |Cite
|
Sign up to set email alerts
|

Study on Wind Simulations Using Deep Learning Techniques during Typhoons: A Case Study of Northern Taiwan

Abstract: A scheme for wind-speed simulation during typhoons in Taiwan is highly desirable, considering the effects of the powerful winds accompanying the severe typhoons. The developed combination of deep learning (DL) algorithms with a weather-forecasting numerical model can be used to determine wind speed in a rapid simulation process. Here, the Weather Research and Forecasting (WRF) numerical model was employed as the numerical simulation-based model for precomputing solutions to determine the wind velocity at arbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…In summary, Table 2 lists all the designed model cases for wind speed (i.e., WIND-1 and WIND-2) and wave height (i.e., WAVE-1 to WAVE-4) and their corresponding algorithms and data used. Here, our proposed cases were WIND-2, WAVE-3, and WAVE-4, and the other cases using past studies were WIND-1 [ 21 , 23 , 29 ], WAVE-1 [ 32 ], and WAVE-2 [ 32 ]. The network architectures of these model cases were described in the following sections.…”
Section: Model Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, Table 2 lists all the designed model cases for wind speed (i.e., WIND-1 and WIND-2) and wave height (i.e., WAVE-1 to WAVE-4) and their corresponding algorithms and data used. Here, our proposed cases were WIND-2, WAVE-3, and WAVE-4, and the other cases using past studies were WIND-1 [ 21 , 23 , 29 ], WAVE-1 [ 32 ], and WAVE-2 [ 32 ]. The network architectures of these model cases were described in the following sections.…”
Section: Model Developmentmentioning
confidence: 99%
“…The influence of wind fields and terrain effects could be considered for more detail. For example, Wei [ 21 ] used the National Center for Environmental Prediction final reanalysis data on 1-degree by 1-degree resolution as the initial field and boundary conditions for simulating a WRF model and suggested that the interpolation method could be used to obtain the spatiotemporal sequences of the wind field effectively. Second, as mentioned earlier, this work collected radar reflectivity images with a sample time of one hour.…”
Section: Conclusion and Suggestionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WRF model provides various options for physical parameters, such as weather patterns, geographic locations, and simulation scenarios. We referred to [17,[67][68][69] in selecting the physical parameters. These researchers studied the typhoon track, rainfall, and wind forecasts for WRF model simulations using reasonable physical parameters for typhoons approaching Taiwan.…”
Section: Wind Field Simulation Using the Wrf Numerical Modelmentioning
confidence: 99%
“…This study reviewed the relevant literature on wind velocity prediction models using DL-based and MLbased approaches, because they exhibit high calculation efficiency and accurate prediction ability (Dongmei et al, 2017;Mallick et al, 2020;Panapakidis et al, 2019;Sheela & Deepa, 2013;Wei, 2014Wei, , 2015. In addition, several popular approaches are investigated such as autoregressive integrated moving average (Cadenas & Rivera, 2010;Cadenas et al, 2016), support vector machine (Chou et al, 2020;Wei, 2017), random forest (Kim et al, 2019), radial basis function (Noorollahi et al, 2016), and neural networks (Chen et al, 2018;Huang et al, 2018a;Hu et al, 2016;Wei, 2019). A recurrent neural network (RNN) is an extension of a conventional feedforward neural network that can handle a variable-length sequence input (Chung et al, 2014;Graves, 2013).…”
Section: Introductionmentioning
confidence: 99%